PENGARUH KINERJA KEUANGAN TERHADAP CAPITAL GAIN PADA INDUSTRI PROPERTI DI BURSA EFEK INDONESIA (PERIODE TAHUN 2008 – 2013) - Ida Wahyuni; Said Djamaluddin (Jurnal Ilmiah Manajemen dan Bisnis, 2016)
This study aims to examine and analyze the effect of Financial Performance ( Current Ratio, Debt to EquityRatio,Total Assets Turn Over and Return on Equity) against Capital Gains on Industrial Property in IndonesiaStock Exchange Data Research is a monthly data for the period of observation for 6 years ( Januari 2008 toDecember 31, 2013). Sampling method used purposive sampling of the population of 40 propertycompanies, 29 companies met the criteria as a sample. The method of analysis used in this study is the technique correlation and regression technique. The results showed Current Ratio, Debt to Equity Ratio,Return on Equity and Total assets Turn Over simultaneously is weak and not significant to Capital Gains isindicated by coefficient of determination ( R2) is 0,044 or 4,4 % while the remaining 95,6 % influenced byother factors. In Partial Liquidity (Current Ratio), Solvency (Debt of Equity Ratio), Activities (Total AssetsTurn Over) effect is weak and insignificant , and Profitability (Return on Equity) effect is weak andsignificant agains Capital Gains .